Spatiotemporal variability in the occurrence of juvenile Japanese jack mackerel Trachurus japonicus along coastal areas of the Kuroshio Current. (7th April 2021) - Ishikawa, Kazuo; Watanabe, Chikako; Kameda, Takahiko; Tokeshi, Tsutomu; Horie, Hikari; Hashida, Daisuke; Ookawa, Toshiyuki; Takeda, Takashi; Kuno, Masahiro; Suzuki, Yuki; Takamura, Shozo; Fukumoto, Ryousuke; et al.
Abstract: To understand the population structure of the Japanese jack mackerel Trachurus japonicus in coastal areas adjacent to the Kuroshio Current (referred to as the "CAK"), we analyzed size composition and commercial landing data of juvenile fish in these areas for the period 2005–2015. Trachurus japonicus does not undergo population‐scale spawning migration, and thus, the connectivity between the spawning and juvenile/adult habitat areas is important. Therefore, our primary aim was to assess the origin of juveniles landed in a number of subareas, including those spawned in local spawning grounds in January–May in the western part of the CAK (w‐CAK), those spawned in May–July in the eastern part (e‐CAK), and those spawned in February–March in the remote spawning ground in the southern East China Sea (s‐ECS). Fishing periods starting in spring (spring onset) were commonly observed in the CAK, which involved relatively small size classes (50–100 mm fork length [FL]). Back estimates based on the growth rate of T .  japonicus suggested that the contributions from the s‐ECS probably dominated most of the spring onsets in April–June because the smallest size class (50–70 mm FL) occurred almost exclusively in April–May. In autumn, onset signals were associated with the landing of juveniles from the local spawning ground in an eastern subarea of the e‐CAK. Despite the asymmetric transport and migration flows between the habitat areas of T .  japonicus, its population levels may be sustained because the local and remote spawning grounds are used in different seasons.